Application of the nature exploration approach based discovery learning model on students learning critical thinking skills and student achievement on plant world in SMA Negeri unggul Banda Aceh - Julia Julia; Khairil Khairil; Supriatno Supriatno (Jurnal Edubio Tropika, 2018)
The purpose of this study was to determine the effect of the application of the nature exploration approach based discovery learning model on students learning critical thinking skills and student achievement. Data were collected in January until March 2017. The method used in this study is an quasi experimental method with pretest posttest control group design. Populations in this research are all student in class X MIPAat SMA Negeri Unggul Kota Banda Aceh is 854 student. The research was conducted in two schools: SMA Unggul Negeri 2 Boarding School and SMA Negeri 10 Fajar Harapan is 161 student. The instrument used was a tests to assess critical thinking skills and student achievement. Data analysis used independent sample t-test and Mann Whitney U Test with SPSS 17.0 for Windows at 0.05 significance level. The result showed that of significant critical thinking skills and students achievement 0,05 is significant 0,000 0,05. Conclusion the application of the nature exploration approach based discovery learning can significant effect that an increase in the ability of critical thinking skills and student achievement in the plant world at SMA Negeri Unggul Banda Aceh.Keywords: The Nature Exploration Approach, Discovery Learning and Plant World.